سيميائية العلامة البصرية في لوحات عامر هاشمي "تسامح مروض" الخط العربي أنموذجا - Pr. Nadia lekdjaa Djalloul Saiah (Journal of Calligraphy, 2023)
The research is concerned with the impact of visual signs in directing the meanings of Arabic calligraphy and its implications as a visible sign, as well as the meaning it carries as a written text. We have followed the semiotic approach to reveal the mechanism of the functioning of signs within a specific format and their role in directing meaning, because semiotics is the science that is concerned with the study of signifiers, whether they are linguistic or visual; The research, then, is classified within the semiotics of the visible. The research seeks to shed light on visual signs such as: lines, shapes, colors, angles, and spaces that produce and give deep meanings to the meanings of Arabic fonts and the meanings of sentences and words. The problem: What are the procedural mechanisms adopted in the interpretation of the meaning of Arabic calligraphy within the framework of the plastic painting? Do the forms formed for the plastic board: colors, graphics, symbols, affect the connotations and suggestions of the line it contains? Is paying attention to the meaning of the speech without paying attention to the significance of the spelling drawing that it carries sufficient to reach the depth of the significance? Among the results of the research: - Visual signs in plastic painting combine with references: religious, cultural, social, ideological, and human experiences to form the meaning of the plastic painting or the meaning of the meaning. . Realizing the meaning of the visual sign is related to the presence of a previous visual culture for the recipient and a visual lexicon, in order to move from the iconic meaning to the semiotic meaning. يهتم البحث بالوقوف على أثر العلامات البصرية في توجيه معاني الخط العربي وتمدللاته بوصفه علامة مرئية فضلا عما يحمله من معنى بوصفه نصا مكتوبا. وقد اتبعنا المنهج السيميائي للكشف عن آلية اشتغال العلامات ضمن نسق معين ودورها في توجيه المعنى، ذلك أن السيميائيات هي العلم الذي يهتم بدراسة الأنساق الدالة سواء أكانت لغوية أم بصرية؛ البحث إذن يصنف ضمن سيمياء المرئي. يسعى البحث إلى تسليط الضوء على العلامات البصرية مثل: الخطوط والأشكال والألوان والزوايا، والمسافات التي تنتج وتضفي دلالات عميقة على معاني الخطوط العربية ومعاني الجمل والكلمات. الإشكالية: ما هي الآليات الإجرائية المعتمدة في تفتيق دلالة الخط العربي داخل إطار اللوحة التشكيلية؟ هل تؤثر الأنساق المشكلة للوحة التشكيلية: ألوان رسومات رموز، في دلالات وإيحاءات الخط الذي تحتويه؟ هل الاهتمام بمعنى الخطاب دون الاهتمام بدلالة الرسم الإملائي الذي يحمله يعد كافيا للوصول إلى عمق الدلالة؟ ومن نتائج البحث: - تتضافر العلامات البصرية في اللوحة التشكيلية بم تحمله من مرجعيات: دينية، ثقافية، اجتماعية، إيديولوجية، وتجارب إنسانية لتشكل معنى اللوحة التشكيلية أو معنى المعنى. إن إدراك معنى العلامة المرئية يرتبط بوجود ثقافة بصرية سابقة لدى المتلقي ومعجما بصريا، قصد الانتقال من المعنى الإيقوني إلى المعنى السيميائي.